2021
DOI: 10.3390/nu13082680
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue “Mediterranean Diet and Metabolic Diseases”

Abstract: The Mediterranean diet (MD) has been considered among the healthiest dietary patterns since a little over 50 years ago, Ancel Keys—as the key figure—provided evidence for the beneficial effects of the MD [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Ardekani et al., in a cross‐sectional investigation, indicated that a higher MIND score was linked to greater insulin sensitivity but not to other metabolic risk factors (Ardekani et al., 2023 ). In this regard, a recent review study reported that high adherence to the Mediterranean diet may lower FBG levels (Magriplis & Chourdakis, 2021 ). A randomized controlled trial study in diabetic patients showed that adherence to the DASH pattern for 12 weeks caused a significant decrease in HbA1C (Daneshzad et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ardekani et al., in a cross‐sectional investigation, indicated that a higher MIND score was linked to greater insulin sensitivity but not to other metabolic risk factors (Ardekani et al., 2023 ). In this regard, a recent review study reported that high adherence to the Mediterranean diet may lower FBG levels (Magriplis & Chourdakis, 2021 ). A randomized controlled trial study in diabetic patients showed that adherence to the DASH pattern for 12 weeks caused a significant decrease in HbA1C (Daneshzad et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diet provided nutrients with major health benefits and was associated with a reduction in noninfectious chronic diseases, neurodegenerative diseases and depression [2,5,26]. The Mediterranean diet has gained global recognition as an eating pattern of great value to medicine and as an important preventive measure and treatment for obesity, metabolic syndrome and related conditions such as cardiovascular disease, type 2 diabetes and neurodegenerative diseases [2,26] (Figure 1). Accessed on 9 May 2024) endorses the Mediterranean diet as one of the healthiest diets for preventing chronic non-infectious diseases such as metabolic syndrome, obesity, cancers, stroke and cardiovascular diseases.…”
Section: What Is the Traditional Mediterranean Diet?mentioning
confidence: 99%
“…Finally, the COVID-19 pandemic and the disruptions of imports from Ukraine and Russia further aggravated the situation of a region in a “post nutrition transition state” [ 14 , 15 ]. The prevalence of undernutrition (wasting, stunting, underweight) and micronutrient deficiencies in some territories is overshadowed by the incidence of overweightness, obesity and diet-related chronic non-communicable diseases with undesirable impacts not only on the health and related public expenditure, but also on the cultural, social, economic, and environmental sustainability dimensions [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%